SKRINNING FITOKIMIA FENOLIK DAN FLAVONOID TOTAL DARI MINYAK ATSIRI SEREH DAPUR (Cymbopogon Cytratus) BUDIDAYA DAERAH WONOSARI BANTUL - YOGYAKARTA - Syahbana, Najwa Nadia (Jurnal Kesehatan Madani Medika, 2025)
Cymbopogon citratus, commonly known as lemongrass, is an aromatic plant widely used for the extraction of essential oils. This study aimed to determine the phytochemical components as well as the total phenolic and flavonoid contents of lemongrass essential oil cultivated in Wonosari, Bantul, Yogyakarta. The essential oil was extracted using the distillation method. Both qualitative and quantitative analyses were performed. Qualitative screening of the essential oils derived from the stems and leaves showed positive results for alkaloids, flavonoids, and phenolic compounds. However, glycosides were detected only in the leaves. Quantitative analysis using a UV–Vis spectrophotometer revealed that the total phenolic content of the essential oil was 0.00041 mg GAE/g, while the total flavonoid content from the leaf extract was 0.00148 mg QE/g. These findings indicate that different parts of the lemongrass plant exhibit distinct chemical characteristics.